Evolutionary origin of peptidoglycan recognition proteins in vertebrate innate immune system - Montaño, Adriana M (BioMed Central, 2011)
BACKGROUND: Innate immunity is the ancient defense system of multicellular organisms against microbial infection. The basis of this first line of defense resides in the recognition of unique motifs conserved in microorganisms, and absent in the host. Peptidoglycans, structural components of bacterial cell walls, are recognized by Peptidoglycan Recognition Proteins (PGRPs). PGRPs are present in both vertebrates and invertebrates. Although some evidence for similarities and differences in function and structure between them has been found, their evolutionary history and phylogenetic relationship have remained unclear. Such studies have been severely hampered by the great extent of sequence divergence among vertebrate and invertebrate PGRPs. Here we investigate the birth and death processes of PGRPs to elucidate their origin and diversity. RESULTS: We found that (i) four rounds of gene duplication and a single domain duplication have generated the major variety of present vertebrate PGRPs, while in invertebrates more than ten times the number of duplications are required to explain the repertoire of present PGRPs, and (ii) the death of genes in vertebrates appears to be almost null whereas in invertebrates it is frequent. CONCLUSION: These results suggest that the emergence of new PGRP genes may have an impact on the availability of the repertoire and its function against pathogens. These striking differences in PGRP evolution of vertebrates and invertebrates should reflect the differences in the role of their innate immunity. Insights on the origin of PGRP genes will pave the way to understand the evolution of the interaction between host and pathogens and to lead to the development of new treatments for immune diseases that involve proteins related to the recognition of self and non-self.